Social and emotional learning competencies and early grade pupils’ academic success: Educational stakeholders’ perspectives - Pambas Basil Tandika; Placidius Ndibalema; Godlove Lawrent (Social and Emotional Learning: Research, Practice, and Policy, 2025)
The influence of social and emotional learning on student academic achievement is widely explored. However, little has been learned about how educators, caregivers and other key educational stakeholders perceive social and emotional learning competencies in relation to early academic success. A qualitative study approach was adopted and individual and focus group interviews were used as data collection tools. A total of 573 participants from Tanzania Mainland and Zanzibar were involved in the study. The main participants were early grade teachers, head teachers, parents and ward educational officers. The gathered data were thematically analysed. The educational stakeholders had varied views regarding social and emotional learning competencies associated with skills that may impact children’s academic subjects. Only skills from three social and emotional learning competencies were regularly mentioned as crucial in achieving this particular role. Capacity strengthening would help educational stakeholders to further identify contextually-relevant social and emotional learning competencies related skills that shape pupils’ academic success.